Colonization with extended spectrum beta-lactamase and carbapenemases producing Enterobacteriaceae among hospitalized patients at the global level: A systematic review and meta-analysis. - Dessie Abera; Ayinalem Alemu; Adane Mihret; Abel Abera Negash; Woldaregay Erku Abegaz; Ken Cadwell (PLoS ONE, 2023)
Background Gut commensal bacteria can mediate resistance against pathogenic bacteria. However, exposure to antibiotics and hospitalization may facilitate the emergence of multidrug resistant bacteria. We aimed to conduct a systematic review and meta-analysis to provide comprehensive evidence about colonization rate of extended spectrum beta-lactamase and carbapenemases producing Enterobacteriaceae. Method We used PubMed, Google Scholar and Web of Science data bases to search studies from January 1, 2016 to August10, 2022 about colonization rate of extended spectrum beta-lactamase and carbapenemase producing Enterobacteriaceae. Data were extracted from eligible studies and analyzed using Stata version 16 software. The quality of included studies was assessed using the Joanna Briggs Institute Critical Appraisal tools, and publication bias was assessed using funnel plot and eggers test. Results We identified 342 studies from the comprehensive data search and data were extracted from 20 studies. The pooled estimate of extended spectrum beta-lactamase and carbapenemase producing Enterobacteriaceae were 45.6%(95%CI: 34.11-57-10) and 16.19% (95% CI: 5.46-26.91) respectively. The predominant extended spectrum beta-lactamase producers were E. coli,32.99% (95% CI: 23.28-42.69) and K. pneumoniae, 11.43% (95% CI:7.98-14.89). Prolonged hospitalization was linked to carbapenemase producing Enterobacteriaceae colonization with the odds of 14.77 (95% CI: -1.35-30.90) at admission and 45.63 (95% CI: 0.86-92.12) after ≥7 days of admission. Conclusion The pooled estimate of extended spectrum beta-lactamase and carbapenemase producing Enterobacteriaceae were high. This indicates the need for strong mitigation strategies to minimize the spread of multidrug-resistant bacteria at the healthcare facilities.